Impact of home parenteral nutrition on family members: A national multi-centre cross-sectional study. Issue 2 (February 2022) - French, Chloe; Lal, Simon; Jones, Debra; Sowerbutts, Anne Marie; Brundrett, Diane; Burch, Nicola; Calvert, Chris; Cooper, Sheldon C.; Donnellan, Clare; Forbes, Alastair; Gabe, Simon; Lam, Ching; et al.
Summary: Background & aims: Home parenteral nutrition (HPN) is a necessary treatment for patients with chronic, type 3, intestinal failure (IF). HPN often requires lifestyle adaptations, which are likely to affect quality of life (QoL) in both patients and family members. The aim of this study was to identify the level of burden on family members who are involved with HPN care and to understand specific factors that contribute to any burden. Methods: Patients over the age of 18 and receiving HPN were identified in IF clinics from multiple centres across the U.K. Eligible patients were asked to complete the parenteral nutrition impact questionnaire (PNIQ) to assess their QoL, while family members were asked to complete the burden scale for family caregivers (BSFC). Logistical regression was undertaken giving adjusted odds ratios (aOR). Results: 678 participants completed the survey representing 339 patients with their appointed family member. Mean PNIQ score was 11.53 (S.D. 5.5), representing a moderate impact of HPN on patients' QoL. On the BSFC scale, 23% of family members reported a moderate to very severe subjective burden indicating an increased risk of psychosomatic symptoms. After adjusting for age and gender, predictors of BSFC included: family members self-reported health status using the EuroQol visual analogue scale (aOR 19.91, 95% CI 1.69, 233.99, p = 0.017) and support received by health services (aOR = 5.83, 95% CI = 1.93, 17.56, p = 0.002). Employment status, disease type, number of nights on HPN and length of time on HPN were not associated with BSFC. Conclusions: Family members with a poor health status or lack of support by health service were more likely to have a moderate to very severe subjective burden. Tailored support from the multi-professional IF team may reduce the burden experienced by family members of people dependent on HPN.